PREVENTION AND MANAGEMENT OF POSTPARTUM INFECTION - Bataglia Araujo, Vicente (2015)
In spite of advances in obstetrics, knowledge of risk causes and use of new and strong antibiotics, puerperal infection is still the main cause of morbidity and mortality of the obstetrical patient (15 percent of maternal deaths in the world). The rate of infections (various ways of presentation) after vaginal labor is about 0,9 – 3,9 percent and after caesarean section up to 10 percent. The etiology of puerperal infection is usually polymicrobial and most of the causal bacteria live in the genital tract of the woman. So in order to avoid its installation it is fundamental to honor asepsis-antisepsis basic standards by attention providers and the limitation of interventions to those necessary for a qualified labor care. Metritis is the uterus infection after labor. Predisposing factors are prolonged labor, PROM, bacterial vaginitis, number of vaginal explorations, forceps use, anemia, and maternal soft tissue traumatism. Antimicrobial therapy, preventive as well as therapeutic, should be founded on evidence based medicine and adequated to the individual patient and institutional attention possibilities. Delay in initiating metritis treatment or its inadequate handling may cause preventable serious complications to women, including death.